Management of pemphigus during covid-19 pandemic era, an experience of single centre - Sahibzada Mahmood Noor, Sahibzada Mahmood Noor; Sagheer, Farah; sardar, adan (Journal of the Pakistan Medical Association, 2025)
The management of pemphigus vulgaris disease was challenging during the coronavirus diseases-2019 pandemic. The current study was planned to determine whether or not rituximab increases the risk and severity of coronavirus diseases-2019 infection in pemphigus vulgaris patients. The retrospective study was conducted at the Lady Reading Hospital, Peshawar, Pakistan, and comprised data from the dermatology unit of 34 diagnosed cases of pemphigus vulgaris who received rituximab treatment from March 2020 to March 2022. The mean age of the patients was 36.58+12.44 years. Majority of patients 28(82.3%) received rituximab as a second-line therapy, while 6(17.64%) were given it as a first-line therapy. Only 1(2.9%) patient developed mild covid pneumonia, and did not need in-patient care or faced oxygen dependence. There was a significant weak association between coronavirus diseases-2019 positivity with age (p=0.000). Rituximab therapy could be given to pemphigus patients during the pandemic, but only when necessary. Key Words: COVID-19, Pemphigus, Severe acute respiratory syndrome coronavirus therapy, Rituximab.